Effect of diets containing raw and processed pigeon pea seed meal supplemented with enzyme on external and internal egg quality characteristics of laying quails Coturnix coturnix japonica - Akintunde, Afolabi Rotimi; Oguntoye, Mutiu Ayogbe; Adeoye, Samson O. B.; Olusiyi, Japhet Adeniyi; Isaac, Samuel; Istifanus, Emmanuel Filian (Syiah Kuala University, 2024)
Three hundred and sixty, six-week old Japanese quail (Coturnix coturnix japonica) hens were used to evaluate the effect of processed pigeon pea seed meal (PPSM) supplemented with enzyme (Vegpro) on egg quality characteristics of laying birds. The processing methods were soaking (24, 48 and 72 hours), fermentation (72 hours), boiling (60 minutes) and roasting (30 minutes). The birds were divided into eight groups of 45 per treatment each replicated three times with 15 birds per replicate in a completely randomized design. Eight experimental diets were formulated containing processed PPSM at 30 % of diet representing T1 (control), T2 (raw PPSM), T3 (soaked PPSM for 24 hours), T4 (soaked PPSM for 48 hours), T5 (soaked PPSM for 72 hours), T6 (soaked PPSM for 24 hours and fermented for 72 hours), T7 (boiling for 60 minutes) and T8 (roasted PPSM for 30 minutes) respectively. The experiment lasted for 20 weeks. Feed and water were provided ad libitum. The results showed that enzyme supplementation of diets containing raw and processed PPSM had no significant (p0.05) effect on egg weight, egg height, egg diameter, egg shape index, egg shell thickness as well as albumen height, albumen diameter, albumen weight, yolk diameter, yolk weight, yolk index and haugh unit across the dietary treatments as these parameters were statistically similar. It was concluded that enzyme supplementation of raw and processed PPSM based diets had no significant effect on the egg quality characteristics of laying quail.